ADAPTIVE SPACE OF JAVANESE TRADITIONAL HOUSE IN BRAYUT TOURISM VILLAGE YOGYAKARTA - Vincentia Reni Vitasurya; Gagoek Hardiman; Suzanna Ratih Sari (TATALOKA, 2019)
Traditional Javanese architecture, especially in rural areas, has undergone a major transformation. Transformation is owner’s response to various conditions, such as the increasing number of family members, the improvement of social status and economic conditions, the needs of modernization and the consequences of being involved in government’s programs.  This paper aim is to examine how the owners of traditional houses respond to nowadays changes reflected through their houses designs. Brayut tourism village is a traditional settlement located at Yogyakarta’s downtown area which is well known for its unique and well-preserved traditional Javanese houses. The transformation of traditional houses in Brayut is a combination of the need for change and persistence. On the one side, strong local traditions play a role in maintaining the elements of traditional houses and on the other side, dynamic modern needs play a role as a trigger for change. Adaptive space in the traditional house is a solution to this problem. The method used in this research is a case study on some Javanese traditional houses. An in-depth interview with the owners and mapping are also used to examine the chronology of traditional houses transformation.  Transformation aspects are defined on the affected physical architecture elements. The result of this study is the transformation occurs on function and meaning of space as an adaptive response from the owners. While the shape of space and buildings, generally preserved as an effort to maintain the bond of traditions and trust.